Planetary atmospheres : From Solar System to exoplanets : atmospheric characterization and search for chemical disequilibrium compounds - Gonçalves, Ruben (2021)
This thesis is based on an ambitious challenge: to provide useful tools in the study and characterization of planetary atmospheres, from the Solar System to exoplanets. There are four steps in the field of planetary atmospheres. Studying Earth’ atmosphere is the first step. The second is the study of Venus’ atmosphere, essential in our understanding of the origin and mechanisms that drive the superrotational atmosphere, the differences between Venus and Earth’s atmosphere and their evolution and what differentiates an Earth-like from a Venus-like exoplanets and how to model and characterize them. The Venus’ cloud-top (70 km) wind results presented in this thesis were retrieved using two techniques: 1) ground-based Doppler Velocimetry (DV), using visible high-resolution spectroscopy (CFHT/ESPaDOnS and TNG/HARPS-N observations) 2) space-based Cloud-Tracking (CT) using UV and visible imaging (VenusExpress/VIRTIS and Akatsuki/UVI observations). The most complete and precise meridional wind profile ever retrieved was based on HARPS-N observations from Gonçalves et al. (2020). Our team has also retrieved zonal wind velocities from Venus’ lower cloud deck (48 km), night-side, using CT on ground-based observations at the TNG/NICS, yielding results consistent with the data provided by space observations. The third and fourth steps of planetary atmospheres study would be the Solar System’s and exoplanet’s atmospheres, respectively. Our team is currently adapting the DV method to measure horizontal winds from Mars, Jupiter and Saturn’s atmospheres. We are also leading ESA’s space mission ARIEL scientific working group “Synergies with Solar System”. Our expertise on SS atmospheres is highly valuable in the context of building a bridge between SS and exoplanets. We are developing a tool that provides an average spectra (point source) using comprehensive coverage data of different SS planets (Venus, Jupiter and Saturn) yielding a proxy of how we would see if those were exoplanets at a chosen distance from Earth.